To pluck up, to tear down a commentary on the book of Jeremiah 1-25 - Brueggemann, Walter (Grand Rapids, MI Eerdmans, 1988)
Includes bibliographical references.
Keywords: Bible. O.T. Jeremiah I-XXV -- commentaries; Bible. O.T. Jeremiah I-XXV -- theology